A Rare Cause of Acute Abdomen in Adults: Adult Intussusception - Muniappan, Sivaneswary; Zainuddin, Zarifa (IIUM Medical Journal Malaysia, 2022)
Adult intussusception is rare, less common and differs from childhood intussusception in its presentation, aetiology and treatment. It is common in paediatrics of less than three years of age.1,2 Unlike in paediatric population, most adult cases presented to emergency department with intestinal obstruction, and rarely, the actual diagnosis of intussusception is made during clinical setting. Top causes of adult intussusception include malignant or benign lesions, post-operative complications such as adhesions, Meckel diverticulum and bowel inflammatory disease. 8-20% of cases are idiopathic with no lead point lesion.3 Preliminary radiograph may show signs of intestinal obstruction, but computed tomography (CT) is the gold standard imaging for intussusception. This is a case report of an adult intussusception in Hospital Tengku Ampuan Afzan, Kuantan which was not detected during clinical examination, but diagnosed by CT imaging.